Two new species of Cystodermella and new combinations in Ripartitella (Agaricineae, incertae sedis) and Cystolepiota (Verrucosporaceae) - Saar, Irja; Cooper, Jerry A.; Trudell, Steven A. (Phytotaxa, 2024)
Two new species of Cystodermella, C. canadensis and C. rubrogranulosa, are described based on phylogenetic and morphological grounds, and compared with similar species. Four holotypes were barcoded: Agaricus terryi, Cystoderma texense, Lepiota sipariana and Melanoleuca vinosa. Two new combinations are proposed: Melanoleuca vinosa as Ripartitella vinosa, and Cystodermella contusifolia as Cystolepiota contusifolia. Cystodermella cristallifera and C. sipariana are found to be conspecific; the older name, C. sipariana, should be adopted and C. cristallifera deprecated as a later synonym. The holotypes of three species: Agaricus terryi, Cystoderma texense and Cystodermella mazahuanensis all represent Cystodermella cinnabarina, for which a neotype is selected.